Catechol/boronic acid chemistry for the creation of block copolymers with a multi-stimuli responsive junction. Issue 28 (24th June 2016) - Coumes, Fanny; Malfait, Aurélie; Bria, Marc; Lyskawa, Joël; Woisel, Patrice; Fournier, David
Abstract : A series of well-defined nitrocatechol and boronic acid end-functionalized homopolymers were synthesized via the RAFT process, followed by their coupling reactions leading to block copolymers integrating a multi-stimuli responsive link in between the blocks. Abstract : Two original Chain Transfer Agents (CTAs) integrating either a nitrocatechol or a boronic acid moiety were synthesized allowing the conception of a wide library of end-functionalized well-defined homopolymers via the Reversible Addition–Fragmentation chain Transfer (RAFT) process. Kinetic studies using NMR spectroscopy and Size Exclusion Chromatography (SEC) were carried out, revealing good control of polymerizations of various monomers. Then, a coupling reaction between the complementary nitrocatechol and boronic acid end-chain polymers was optimized to create a dynamic boronate ester junction between the polymer blocks. The effectiveness of the reaction was demonstrated by means of NMR ( 1 H, DOSY), SEC and cyclic voltammetry. The ability of the covalent bond, and thus the block copolymers, to be disrupted on demand was assessed using a competitive molecule (2-naphthylboronic acid) and UV irradiation as stimuli.